ASSOCIATION BETWEEN PRO BRAIN NATRIURETIC PEPTIDE AND LENGTH OF STAY IN PATIENTS WITH SEPSIS. - Shahid Hamid1, Asadullah Nawazani2, M. Jamshaid Khan3, Farid Ullah Khan4, Almas Parkar5, Nayab Mustafa6, Sarah SalahAldin7, Sherin Marina Varghese8, Dania Shahzad9, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT INTRODUCTION: Sepsis is the third major cause of mortality worldwide, with heart disease and cancer ranking first and second respectively. N-terminal pro-Brain Natriuretic Peptide (NT-proBNP) is a cardiac-overload biomarker associated with cardiovascular disease and sepsis severity3,4. This study was conducted to discover the prognostic significance of proBNP in patients with sepsis but no evidence of heart disease, with respect to length of hospital stay. METHODS: Patients admitted to Dubai Hospital between August 2017 and April 2019, with a diagnosis of sepsis or septic shock and without any prior history ofcardiac illnesses, were included in this study. ProBNP levels were tested within 48-72 hours of admission and results were analysed to look for its prognostic value in terms of length of hospital stay. Cross tabulation using Fisher’s exact score was carried out between proBNP level, categories of PCT level and ethnicity of patient’s with length of stay. Data was analysed retrospectivelyusing SPSS software. RESULTS: A total of 48 patients were analysed. 67% were males and 33% were female. The median age was found to be 72.5 years. 58% of patients were from the Middle East and Africa (MENA) region, 35% from Asia, 4% from Europe and for 3% ethnicity was not recorded. 4.2% of the patients had normal levels of Pro-BNP, 16.7% had moderate levelsand 79.2% had markedly high range. 25 % of the patients had mild levels of PCT, 17% had moderate levels, and 58% had markedly increased levels of PCT. 6.3% of patients discharged within 72 hours, 81.3% got discharged after 72 hours and 12.5% of the patients deceased during hospitalization. This study was unable to establish a significant relation between pro-BNP levels and length of hospital stay (p=0.279). Statistically significant relation was found between ethnicity and length of hospital stay with a p-value of 0.04. CONCLUSION: This study did not show strong association between proBNP and prognosis in terms of length of hospital stay in septic patients in the absence of previous cardiac diseases.